Psihološke posledice pandemije COVID-19 na zdravstvene delavce - Jurjevčič Tržan, Maja (Rehabilitacija (Ljubljana), 2021)
This article presents the potential effects of a pandemic on mental health and lists the key risk factors for the occurrence of psychological distress. During major outbreaks of infectious diseases, the level of stress significantly rises, which also increases the incidence of intense unpleasant emotional states, symptoms of anxiety and depression, and post-traumatic stress. Some groups are particularly at risk for negative psychological consequences, such as individuals who become infected or ill during a pandemic, those with pre-existing mental health problems, and health professionals who are further exposed to dangerous situations at work. Studies show that health workers most often face fear, anxiety and depression, experience insomnia and post-traumatic stress, with frontline health workers being more at risk for developing psychological distress. In frontline workers, the key risk factors for mental distress are associated with extraordinary workload, lack of protective equipment, self-doubt and lack of knowledge of infection control, and many ethical dilemmas regarding the treatment of patients. The key to addressing the psychological consequences of a pandemic is the development of systemic interventions, which should primarily include access to reliable information, mechanisms of psychological first aid, education and training of constructive coping strategies, and healthy lifestyle promotion. Regarding the need to promote social isolation to prevent the spread of the infection, there is also a growing need to establish effective technological and online solutions.
Keywords: COVID-19; dejavniki tveganja; duševna stiska; early interventions; health crisis; Health Personnel; healthcare workers; psychological distress; psychology; risk factors; zdravstvena kriza; zdravstveni delavci; zgodnje posredovanje